Phrasal Verbs in English and Arabic: A Contrastive Study With Reference to Some Scientific Texts أشباه الجمل الفعلية باللغتين العربية والإنجليزية: دراسة مقارنة مع الإشارة إلى بعض النصوص العلمية - Louhaz Abdul Amir Mubarak لحاظ عبد الأمير مبارك (Journal Of Babylon Center For Humanities Studies, 2015)
Introduction Phrasal verb, in both English and Arabic languages can be defined as a type of verb consisting of a sequence of a lexical elements. English phrasal verbs could be transitive or intransitive e.g. come in, get up, look out for, subtype may be distinguished on syntactic grounds into separable and inseparable. The particles may be classified into prepositional or adverbial types. Arabic language includes a linguistic item that shares some features of English phrasal verbs (often called prepositional verbs). Arabic phrasal verbs are classified as a subtype of transitive verbs. Transitive verbs in Arabic are classified into two types: transitive by itself such as يلقي in ﴿وَأَلْقِ عَصَاكَ﴾ (النمل: 10); and transitive through a preposition such as يعشو in وَمَن يَعْشُ عَن ذِكْرِ الرَّحْمَنِ نُقَيِّضْ لَهُ شَيْطَانًا فَهُوَ لَهُ قَرِين﴾) (الزخرف: 36) this later type is parallel to the English phrasal verbs. The present study is an attempt to show the syntactic and semantic aspects of phrasal verbs in both English and Arabic to find out the similarities and differences between the two languages in relation to this type of verbs.